Towards Enhancing EFL Learner Autonomy in the Algerian Secondary School - FEDJ, samia (Bouhass Benaissi Fawzi, 2020)
Based upon an educational philosophy that promotes the idea of preparing learners as independent responsible citizens instead of global human capital and following the strong belief in the significance of self-initiated learning in improving the quality of foreign language education, this research aims to explore ways and approaches that can foster autonomous practice in the Algerian EFL context. It intends to lead a controlled group of EFL secondary school pupils gradually towards taking greater responsibility for their own learning and aims to assist them in becoming moderately autonomous. In order to attain this purpose, an action research served as the optimal method owing to its practicality and feasibility. In the course of the investigation, questionnaires, interview and class observation were utilized as data collection instruments in order to enable the researcher analyze and evaluate the findings both quantitatively and qualitatively. Pupils’ perceptions and attitudes towards different aspects of autonomous learning were examined prior to and after carrying out the action research. The current thesis consists of five chapters covering both theoretical and practical parts. The theoretical section sheds light on the concept of learner autonomy in relation to the most relevant notions posited in the literature, as it examines the position of autonomy within the Algerian educational setting. Whereas, the practical part attempts to investigate, implement and assess multiple teaching techniques and strategies for enhancing autonomous learning in the immediate class environment. In fact, the obtained findings displayed that most participants did not exhibit a quite remarkable enhancement in autonomy levels. However, they started developing particular basic autonomous skills such as: awareness of the learning goals and strategies, the capacity for detachment in specific learning activities and the practice of some self-evaluation techniques. Consequently, drawing from the study findings and a number of amendments in the implemented pedagogy, a set of recommendations and pedagogical implications were put forward to social agents, curriculum designers and EFL secondary school mentors at the aim of facilitating the gradual integration and development of autonomy in the Algerian EFL classroom.
The Case of First and Second Year
Keywords: Learner Autonomy, English as a Foreign Language, Secondary School in Algeria.